Association between sex hormones regulation‐related SNP rs12233719 and lung cancer risk among never‐smoking Chinese women - Qian, Ying (Cancer Med, 2021)
BACKGROUND: The mechanism of rapidly increased non‐small cell lung cancer (NSCLC) among never‐smoking Chinese women has not been elucidated. Ovarian sex steroid hormones have been suggested to counteract lung cancer development, and sex hormone‐binding globulin (SHBG) is essential in sex hormones regulation. This study aims to exploring single nucleotide polymorphisms (SNPs) in genomic regions associated with SHBG concentrations that contributed to never‐smoking female NSCLC. METHODS: Candidate genes were selected by a genome‐wide association (GWAS) meta‐analysis and gene expression profiles of never‐smoking NSCLC of Chinese women. The candidate SNPs limited to common minor allele frequency (MAF), missense variant, ethnic heterogeneous distribution, and SNPs were genotyped using the TaqMan method. A two‐stage case‐control design was adopted for exploration and validation of associations between candidate SNPs and risk of NSCLC. All participants were never‐smoking Chinese women. Chi‐square test and multivariate logistic regression were applied. RESULTS: Beginning with 12 genomic regions associated with circulating SHBG concentrations and gene expression profiles from never‐smoking NSCLC in Chinese women, candidate SNP rs12233719 and rs7439366 both located in candidate gene UGT(2)B(7,) which may be related to circulating SHBG concentrations and cancer risk, were identified. A two‐stage case‐control study was conducted in Shenyang and Tianjin represented as the training stage and validation stage, respectively. Under the dominant model, compared to individuals with the wild G/G genotype, the adjusted OR of those with the T allele was 1.58 (95% CI: 1.15–2.16) in Chinese Shenyang training set, and was 1.49 (95% CI: 1.02–2.18) in Chinese Tianjin validation set, both accompanied with a significant trend relationship consistently. UGT2B7 was upregulated in female NSCLC patients’ tumor tissues and was associated with a poor prognosis in NSCLC. CONCLUSION: Our findings indicated that a sex hormones regulation‐related SNP rs12233719 was associated with never‐smoking female lung cancer risk, which might partially explain NSCLC‐susceptibility in Chinese women.